Strategiczny wymiar rachunku kosztów docelowych - Masztalerz, Marek (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The progressing globalisation made the economic environment unstable and unpredictable. Consequently, the amount of data needed to take right decisions in the global market increased significantly. Companies, in order to survive in a very fierce competition and remain profitable, became market and customer oriented. They were forced to look for innovative solutions such as strategic management and target cost management. This article explores strategic traits of target costing. The purpose of this paper is to show that target costing may be successfully used as strategic management tool for attaining and sustaining the strategic advantage. The very essence of target costing as cost calculation process and management system is presented. Long term (life cycle) planning, strategic product characteristics, strategic survival triplet and value chain analysis are described as the proofs of strategic dimension of target costing. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1080, s. 250-258